2013
DOI: 10.1016/j.neurobiolaging.2013.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in resting connectivity with age: a simultaneous electroencephalogram and functional magnetic resonance imaging investigation

Abstract: Resting fluctuations in the blood oxygenation level-dependent signal have attracted considerable interest for their sensitivity to pathological brain processes. However, these analyses are susceptible to confound by nonneural physiological factors such as vasculature, breathing, and head movement which is a concern when investigating elderly or pathological groups. Here, we used simultaneous electroencephalogram (EEG) and functional magnetic resonance imaging (fMRI) (EEG/fMRI) to constrain the analysis of rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 84 publications
3
32
1
Order By: Relevance
“…In line with the present findings, a combined EEG/fMRI study also found opposing age-activity relations for cortical DMN and the HC (28), with an age decrease in cortical DMN beta power along with an age increase in HC beta power. The basis for differential influences of advancing age on key components of the DMN remains to be determined.…”
Section: Hippocampus Proper As Segmented By Freesurfersupporting
confidence: 91%
See 2 more Smart Citations
“…In line with the present findings, a combined EEG/fMRI study also found opposing age-activity relations for cortical DMN and the HC (28), with an age decrease in cortical DMN beta power along with an age increase in HC beta power. The basis for differential influences of advancing age on key components of the DMN remains to be determined.…”
Section: Hippocampus Proper As Segmented By Freesurfersupporting
confidence: 91%
“…In addition, aging may affect cardiovascular dynamics, and although ICA can help to disentangle such confounding variables from RSNs, it cannot be ruled out that the observed differences in RSNs at least in part reflected nonneural factors. Critically, however, the related observation of an age-related EEG increase in HC RSN activity (28) suggests that our finding of an age-related increase in HC-fMRI connectivity has a neural origin. We used ICA components to define RS networks (defined as spatially independent but temporally correlated sets of regions), but note that there are various ways to characterize and estimate networks.…”
Section: Hippocampus Proper As Segmented By Freesurfercontrasting
confidence: 51%
See 1 more Smart Citation
“…In a similar vein, these results provide evidence against the notion that the observed reduction in BOLD activation in older adults during the resting state is due to age-related differences in cerebral vasculature alone (Bangen et al, 2009;D'Esposito, Deouell & Gazzaley, 2003;Kannurpatti et al, 2010 (Balsters et al, 2013).…”
Section: Discussionsupporting
confidence: 49%
“…(2013). In order to account for differences in breathing and heart rate across age‐groups, and individuals, we collected both respiratory and cardiac pulse data for all participants and regressed these from participant's functional data.…”
Section: Discussionmentioning
confidence: 99%